Applying indigenous knowledge resources in children’s play-crafting in Southern Nigeria : practice-led research using Ibibio folk narratives - Inyang, Idaresit Ofonime (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2021.